Cost-Effectiveness of Nivolumab Plus Ipilimumab With and Without Chemotherapy for Advanced Non-Small Cell Lung Cancer - Yang, Szu-Chun; Kunst, Natalia; Gross, Cary P.; Wang, Jung-Der; Su, Wu-Chou; Wang, Shi-Yi (Frontiers in Oncology, 2021)
Background First-line treatment with nivolumab plus ipilimumab (N+I) or nivolumab plus ipilimumab with two cycles of chemotherapy (N+I+chemotherapy) improve overall survival and progression-free survival for patients with metastatic non-small cell lung cancer (NSCLC), yet researchers have not concomitantly compared the cost-effectiveness of N+I and N+I+chemotherapy with chemotherapy alone. Materials and methods Using outcomes data from the CheckMate 227 and CheckMate 9LA phase 3 randomized trials, we developed a Markov model with lifetime horizon to compare the costs and effectiveness of N+I and N+I+chemotherapy versus chemotherapy from the U.S. health care sector perspective. Subgroup analysis by programmed death-ligand 1 (PD-L1) expression levels (≥1% and <1%) and probabilistic analysis were performed. Results The incremental cost-effectiveness ratio (ICER) of N+I versus chemotherapy was 239,072 per QALY, and 838,198 per QALY for N+I+chemotherapy versus N+I. The ICER of N+I versus chemotherapy was 246,584 per QALY for patients with PD-L1 ≥ 1% and 185,620 per QALY for those with PD-L1 < 1%. In probabilistic analysis, N+I had a 2.6% probability of being cost-effective at a willingness-to-pay threshold of 150,000 per QALY. The probability was 0.4% for patients with PD-L1 ≥ 1% and 10.6% for patients with PD-L1 < 1%. Conclusion First-line N+I or N+I+chemotherapy for metastatic NSCLC was not cost-effective regardless of PD-L1 expression levels from the U.S. health care sector perspective.